Implementasi Terapi Spiritual Emotional Freedom Technique (SEFT) Untuk Menurunkan Kecemasan Pada Pasien Pre-Operasi - Finka Hanandayu Kawanda; Ambar Relawati (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background: Pre-operative anxiety is the fear of pain after surgery, physical changes, facing surgical equipment and staff, death during anesthesia, failure of surgery or complications during surgery. Anxiety in patients who will undergo surgery can be overcome with non-framacological therapy, namely SEFT therapy which has a positive impact on reducing preoperative patient anxiety. Purpose: This case study aims to determine whether implementing SEFT therapy can reduce anxiety in preoperative patients Method : The method is a case study focusing on one patient. First, a numerical rating scale was utilised to measure the intensity of anxiety of the patients using the STAI (State-Traite Anxiety Inventory), then using SEFT therapy over of 3 stages, namely set-up, tune-in, and tapping between 10-15 minutes 1 time per day for 2 days, then re-evaluate using STAI to measure anxiety levels after the intervention Results: The results show that using the SEFT therapeutic intervention, the preoperative patient's anxiety level decreased from moderate anxiety to mild anxiety Suggestion: Nurses could provide education to patients and their families in order to be able to reduce anxiety in the pre-operative phase so that patients can become more relaxed and comfortable.